Japanese Soft Power in Indonesia on Anime Entitled Ufo Baby: Study of Popular Culture - Risa Yuliani; R.M. Mulyadi; M. Adji (IZUMI, 2021)
Anime as Japanese popular culture has been successfully consumed by mass in many countries. It indicates that Japan's strategy to make anime one of its soft power has been successfully accepted by the world community. In Indonesia, since anime entered the television, the enthusiasm given by the community has been good and positive. Anime is liked by various circles, especially children, even today. Ufo Baby is one of the shows on RCTI, even though it's not as global as Doraemon, for example, but apart from an interesting storyline, this anime also incorporates many elements of Japanese culture. The aim of this study is to explain the soft power of Japan in Indonesia on anime entitled “Ufo Baby”. The research method uses a qualitative approach with interpretive analysis. The researched part is scenes from anime that contain cultural elements. The approach used is John Storey's cultural theory and Nye Joseph's theory of soft power. Data collection was conducted to examine the influence of Japanese culture on Indonesian society by using interview techniques. The results of this study reveal that in the Ufo Baby anime there are elements of soft power culture used by Japan. From the results of research, the culture shown in anime has an influence on Indonesian society marked by the community's participation in celebrating traditional Japanese festivals and the discovery of many typical Japanese goods sold in local shops.